Circuit racing, track texture, temperature and rubber friction. Issue 4 (2nd April 2016) - Sharp, R. S.; Gruber, P.; Fina, E.
ABSTRACT: Some general observations relating to tyre shear forces and road surfaces are followed by more specific considerations from circuit racing. The discussion then focuses on the mechanics of rubber friction. The classical experiments of Grosch are outlined and the interpretations that can be put on them are discussed. The interpretations involve rubber viscoelasticity, so that the vibration properties of rubber need to be considered. Adhesion and deformation mechanisms for energy dissipation at the interface between rubber and road and in the rubber itself are highlighted. The enquiry is concentrated on energy loss by deformation or hysteresis subsequently. Persson's deformation theory is outlined and the material properties necessary to apply the theory to Grosch's experiments are discussed. Predictions of the friction coefficient relating to one particular rubber compound and a rough surface are made using the theory and these are compared with the appropriate results from Grosch. Predictions from Persson's theory of the influence of nominal contact pressure on the friction coefficient are also examined. The extent of the agreement between theory and experiment is discussed. It is concluded that there is value in the theory but that it is far from complete. There is considerable scope for further research on the mechanics of rubber friction.